Checking cat diseases symptoms system using rule-based technique - Nur Idayu, Samat (2010)
Checking Cat Diseases Symptoms System Using Rule-based Technique (CCDS) is a system that mimics the role played by a veterinarian to diagnose cat disease. CCDS is aimed to change manual disease diagnosis into computerized and recommendation the solution for the treat the disease. The purpose of CCDS is to save cat owner's time, energy and money. User need to answer questionnaire to diagnose what disease is suffering by their cat and to know the solution. The prototype of this system use rule-based expert system technique. This technique will replace most of the human task and can determine the solution for treat cat disease based on rules and constraints.